2014
DOI: 10.1002/adma.201306097
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Plasmon Resonances in Two‐Dimensional Molybdenum Oxide Nanoflakes

Abstract: appreciable free carrier concentration. [5][6][7] The same strategy can potentially be implemented in selected 2D semiconductors. Another concern is the damping losses that should be kept low for applications such as optical communications, in which a long propagation of waves is necessary. [ 7 ] Reducing such damping losses requires that the product of the effective electron mass and the free charge mobility must be large in the 2D material. As a result, fi nding favorable materials that satisfy the aforement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
349
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 331 publications
(366 citation statements)
references
References 41 publications
14
349
2
1
Order By: Relevance
“…Finally, we note that while we focus on the production of graphene using this method, it can easily be extended to exfoliate inorganic layered compounds such as BN, MoS 2 or MoO 3 . 32,[43][44][45] It is important to note that the value of this work is not the demonstration that kitchen blenders can be used to produce graphene, although this may be a useful result. Rather, this work shows that industrial rotating blade stirred tank reactors are a promising new technology for large scale graphene production.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we note that while we focus on the production of graphene using this method, it can easily be extended to exfoliate inorganic layered compounds such as BN, MoS 2 or MoO 3 . 32,[43][44][45] It is important to note that the value of this work is not the demonstration that kitchen blenders can be used to produce graphene, although this may be a useful result. Rather, this work shows that industrial rotating blade stirred tank reactors are a promising new technology for large scale graphene production.…”
Section: Resultsmentioning
confidence: 99%
“…8,23 Such dispersions can be used to process the nanosheets into functional structures such as films, networks and composites. 20,[24][25][26] Such structures have proven useful in a range of application areas including plasmonics, 27 photodetectors, 24,28,29 electrodes in dye-sensitised solar cells, 30 supercapacitors 31 and batteries 26,32 or electro-catalysts 33 for hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%
“…MoO 3 nano-akes have been used for hydrogen gas (H 2 ) sensing, photoluminescence and eld emission. [24][25][26] Recently, Alsaif et al 27 demonstrated tunable plasmon resonances from 2D MoO 3 nano-akes. These reports have shown the potential of MoO 3 nano-akes; however, their application in devices is required to further prove their potential.…”
Section: -25mentioning
confidence: 99%
“…The most successful methods are the modied hot plate method, 25 the plasma assisted paste sublimation process, 35 the organic solvent assisted grinding and sonication method, 26,27 etc. Here, we adapted the organic solvent-assisted grinding and sonication method of liquid exfoliation to bulk MoO 3 to obtain 2D nano-akes.…”
Section: -25mentioning
confidence: 99%
See 1 more Smart Citation